ULACNet-301, OPTIMO protocol: optimizing HPV vaccination regimen for cancer prevention in children and adolescents living with HIV - Delia Pinto-Santini; Emilia M. Jalil; Giovana Teixeira Fernandes; Genevieve Hilaire; Lenka Kolevic; Robinson Cabello; Beatriz Grinsztejn; William Pape; Marie Marcelle Deschamps; Margaret G. House; Emma Brofsky; Vikrant V. Sahasrabuddhe; et al. (BMC Cancer)
Abstract Background Persistent infection with human papillomavirus (HPV) is associated with most cervical and anal cancer cases and a large fraction of other anogenital and oropharyngeal cancers. The prophylactic HPV vaccines are known to prevent HPV infections and HPV-associated disease, although there is evidence of reduced response to the HPV vaccination among individuals living with HIV. Prior studies among individuals without HIV suggest that a single HPV vaccine dose induces humoral immune responses that, while lower than those induced by two or three doses, still confer protection against HPV infection. Current recommendations for HPV vaccine include a single-dose schedule for children 9–14-years-olds without HIV. Although two to three doses are recommended for children living with HIV (CLWH), there is very limited data comparing responses to one vs. 2–3 doses in CLWH. Methods The OPTIMO study will compare immune responses to HPV vaccination in CLWH by measuring antibody and memory B cell (Bmem) responses after 1, 2, or 3 doses of the 9-valent HPV (9vHPV) vaccine, Gardasil-9. A comparison group of children without HIV will receive one dose of the vaccine. The durability of the response will be assessed at 24 months after the last dose of a given regimen. The OPTIMO trial will take place among CLWH from low and middle-income country (LMIC) settings in Peru, Brazil, and Haiti. Discussion Previous studies of single-dose regimens in individuals without HIV raise questions about whether one dose would suffice for CLWH and, if not, whether two or three doses are needed to provide protection against HPV-related cancers. These questions have operational consequences in LMICs given the barriers to delivering multiple doses, uneven availability, and intermittent shortages of HPV vaccines. In addition, information on HIV status for children and adolescents is rarely available during vaccination campaigns based in schools or public health clinics, so CLWH may receive a single dose despite policy recommendations that they receive two or three. This study will provide evidence on the optimal number of doses needed for CLWH that can inform HPV vaccination campaigns in LMICs, especially those with a higher burden of HIV infection and higher incidence of HPV-related cancers. Trial registration ClinicalTrials.gov NCT04265950.